Pengaruh Pemberian Daun Katuk terhadap Produksi ASI pada Ibu Nifas - Rionita; Puspita, Rika; Yanti, Rifa; Tanberika, Fajar Sari (Universitas Muhammadiyah Surabaya, 2026)
Background: Exclusive breastfeeding is a global strategy to improve infant growth, development, health, and survival. One way to increase breast milk supply is by improving the quality of foods that directly influence milk production, namely katuk leaves. Purpose: To determine the effect of katuk leaf administration on breast milk production in postpartum mothers. Methods: The type of research used was a quasi-experimental study with a one-group pre-test post-test design. The sample in this study used a purposive sampling technique of 22 postpartum mothers at Meranti Regional Hospital using the Slovin formula. The analysis used a paired sample t-test. Results: The results of the study on breast milk production of postpartum mothers before giving boiled katuk leaves were that breast milk production was low for 15 respondents (68.2%) and breast milk production after giving boiled katuk leaves was high for 22 respondents (100%). The results of the paired sample t-test showed a p value = 0.000 <α = 0.05, where Ha was accepted, meaning that there was an effect of giving boiled katuk leaves on breast milk production in postpartum mothers Conclusion: There is an effect of giving boiled katuk leaves on breast milk production in postpartum mothers